2016
DOI: 10.4172/pharmaceutical-sciences.1000167
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted Extraction and RP-HPLC Quantification of Bergapten from Pithecellobium dulce

Abstract: A comparative extraction efficiency study was performed for microwave assisted and other conventional extraction techniques. An accurate, precise and validated reverse phase high-performance liquid chromatography method was developed for estimation of bergapten from Pithecellobium dulce. Several parameters which can potentially affect the extraction yield, namely extraction technique, microwave power, extraction time and solid-liquid ratio were studied. The extraction conditions of microwave assisted extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Besides, it has also been found that MAE is compatible with water as an extraction solvent so that the use of organic solvents is reduced/eliminated, and more medium- and non-polar organic compounds from plant materials could also be extracted by MAE [ 25 , 26 , 27 ]. Moreover, MAE as a sample preparation method could be coupled with some chromatography and spectroscopy tools, such as HPLC and GC-MS, to achieve rapid determination with satisfactory precision and recovery [ 28 , 29 , 30 ]. Therefore, MAE has been used in the extraction of several bioactive components from natural products [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it has also been found that MAE is compatible with water as an extraction solvent so that the use of organic solvents is reduced/eliminated, and more medium- and non-polar organic compounds from plant materials could also be extracted by MAE [ 25 , 26 , 27 ]. Moreover, MAE as a sample preparation method could be coupled with some chromatography and spectroscopy tools, such as HPLC and GC-MS, to achieve rapid determination with satisfactory precision and recovery [ 28 , 29 , 30 ]. Therefore, MAE has been used in the extraction of several bioactive components from natural products [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous compounds have been identified in G. sepium [10][11][12][13][14], including Leucaena leucocephala (L. leucocephala) [15][16][17][18][19] and Pithecellobium dulce (P. dulce) [20][21][22][23]. However, the anthelmintic effect on H. contortus and the composition of the most active extract partitions of the species G. sepium, L. leucocephala, and P. dulce, which grow in a tropical dry forest (TDF) environment, are not known.…”
Section: Introductionmentioning
confidence: 99%